A Short History of Atomic Layer Deposition: Tuomo Suntola's Atomic Layer Epitaxy2. Issue 10 (15th October 2014) - Puurunen, Riikka L.
Abstract: Atomic layer deposition (ALD) is a thin film growth technique based on the repeated use of separate, saturating gas‐solid reactions. The principle of ALD has been discovered twice; in the 1960s under the name "molecular layering" in the Soviet Union, and in the 1970s under the name "atomic layer epitaxy" (ALE) in Finland. In 2014, it is forty years since the filing of the worldwide patent on ALE as a method for the growth of compound thin films. This essay celebrates the fortieth anniversary of ALE‐ALD, briefly telling the story of ALE as shared by its Finnish inventor, Dr. Tuomo Suntola. Initially, ALE was aimed at the growth of high‐quality polycrystalline ZnS thin films for electroluminescent (EL) display panels. Gradually, the material selection of ALE increased, and the application areas were extended to photovoltaics, catalysis, semiconductor devices, and beyond. Fast, production‐worthy ALE reactors were imperative for industrial success. The unprejudiced creation of new technologies and products with ALE, initiated by Dr. Tuomo Suntola and led by him until early 1998, are an integral part of the Finnish industrial history, the fruits of which are seen today in numerous applications worldwide. Abstract : This essay celebrates the fortieth anniversary of ALD in Finland, telling the story of ALE as shared by its inventor, Dr. Tuomo Suntola. The creation of new technologies and products with ALE‐ALD, initiated by Dr. Tuomo Suntola and led by him until early 1998, are an integral part of the Finnish industrial history, the fruits of which are seen forty years later in numerous applications worldwide.